Concurrent Use in Taiwan of Chinese Herbal Medicine Therapies among Hormone Users Aged 55 Years to 79 Years and Its Association with Breast Cancer Risk: A Population-Based Study. (29th May 2014) - Tsai, Yueh-Ting; Lai, Jung-Nien; Wu, Chien-Tung; Lin, Shun-Ku
Abstract : Background . The purpose of the present study was to analyze the concurrent use of Chinese herbal products (CHPs) among women aged 55 to 79 years who had also been prescribed hormonal therapies (HT) and its association with breast cancer risk. Methods . The use, frequency of service, and CHP prescribed among 17, 583 HT users were evaluated from a random sample of 1 million beneficiaries from the National Health Insurance Research Database. A logistic regression method was used to identify the factors that were associated with the coprescription of a CHP and HT. Cox proportional hazards regressions were performed to calculate the hazard ratios (HRs) of breast cancer between the TCM nonusers and women who had undergone coadministration of HT and a CHP or CHPs. Results . More than one out of every five study subjects used a CHP concurrently with HT (CHTCHP patients). Shu-Jing-Huo-Xie-Tang was the most commonly used CHP coadministered with HT. In comparison to HT-alone users, the HRs for invasive breast cancer among CHTCHP patients were not significantly increased either in E-alone group or in mixed regimen group. Conclusions . The coadministration of hormone regimen and CHPs did not increase the risk of breast cancer.